Тoponyms in the Kazakh and Turkish languages - Нaзaровa А. Ж. (Journal of Oriental Studies, 2017)
The article deals with morphological structure of place names in Russian and Kazakh languages. In Kazakh and Russian languages, the composition and structure of names is a complex process. Morphological structure of place names is closely connected with the rules of word formation of the language. Word-building means not only the formation of new words but also a semantic change. In the process of creating place names in Russian and Kazakh languages are used all the ways of word formation. Place names the same as the derivative words are formed through three main ways of word formation.